Combining hyperpolarized 13C MRI with a liver‐specific gadolinium contrast agent for selective assessment of hepatocyte metabolism. Issue 6 (14th June 2016) - Ohliger, Michael A.; von Morze, Cornelius; Marco‐Rius, Irene; Gordon, Jeremy; Larson, Peder E. Z.; Bok, Robert; Chen, Hsin‐yu; Kurhanewicz, John; Vigneron, Daniel
Abstract : Purpose: Hyperpolarized 13 C MRI is a powerful tool for studying metabolism, but can lack tissue specificity. Gadoxetate is a gadolinium‐based MRI contrast agent that is selectively taken into hepatocytes. The goal of this project was to investigate whether gadoxetate can be used to selectively suppress the hyperpolarized signal arising from hepatocytes, which could in future studies be applied to generate specificity for signal from abnormal cell types. Methods: Baseline gadoxetate uptake kinetics were measured using T1 ‐weighted contrast enhanced imaging. Relaxivity of gadoxetate was measured for [1‐ 13 C]pyruvate, [1‐ 13 C]lactate, and [1‐ 13 C]alanine. Four healthy rats were imaged with hyperpolarized [1‐ 13 C]pyruvate using a three‐dimensional (3D) MRSI sequence prior to and 15 min following administration of gadoxetate. The lactate:pyruvate ratio and alanine:pyruvate ratios were measured in liver and kidney. Results: Overall, the hyperpolarized signal decreased approximately 60% as a result of pre‐injection of gadoxetate. In liver, the lactate:pyruvate and alanine:pyruvate ratios decreased 42% and 78%, respectively ( P  < 0.05) following gadoxetate administration. In kidneys, these ratios did not change significantly. Relaxivity of gadoxetate for [1‐ 13 C]alanine was 12.6 times higher than relaxivity of gadoxetate for [1‐ 13 C]pyruvate, explaining the greater selective relaxation effect on alanine. Conclusions: The liver‐specific gadolinium contrast‐agent gadoxetate can selectively suppress normal hepatocyte contributions to hyperpolarized 13 C MRI signals. Magn Reson Med 77:2356–2363, 2017. © 2016 International Society for Magnetic Resonance in Medicine